The protective role of autophagy in nephrotoxicity induced by bismuth nanoparticles through AMPK/mTOR pathway. Issue 6 (3rd July 2018) - Liu, Yongming; Yu, Huan; Zhang, Xihui; Wang, Yong; Song, Zhentao; Zhao, Jian; Shi, Haibin; Li, Ruibin; Wang, Yangyun; Zhang, Leshuai W.
Abstract: Bismuth is widely used in metallurgy, cosmetic industry, and medical diagnosis and recently, bismuth nanoparticles (NPs) (BiNP) have been made and proved to be excellent CT imaging agents. Previously, we have synthesized bovine serum albumin based BiNP for imaging purpose but we found a temporary kidney injury by BiNP. Due to the reported adverse events of bismuth on human health, we extended our studies on the mechanisms for BiNP induced nephrotoxicity. Blood biochemical analysis indicated the increase in creatinine (CREA) and blood urea nitrogen (BUN), and intraluminal cast formation with cell apoptosis/necrosis was evident in proximal convoluted tubules (PCTs) of mice. BiNP induced acute kidney injury (AKI) was associated with an increase in LC3II, while the autophagic flux indicator p62 remained unchanged. Chloroquine and rapamycin were used to evaluate the role of autophagy in AKI caused by BiNP. Results showed that BiNP induced AKI was further attenuated by rapamycin, while AKI became severe when chloroquine was applied. In vitro studies further proved BiNP induced autophagy in human embryonic kidney cells 293, presented as autophagic vacuole (AV) formation along with increased levels of autophagy-related proteins including LC3II, Beclin1, and Atg12. Specifically, reactive oxygen species (ROS) generated by BiNP could be the major inducer of autophagy, because ROS blockage attenuated autophagy. Autophagy induced by BiNP was primarily regulated by AMPK/mTOR signal pathway and partially regulated by Akt/mTOR. Our study provides fundamental theory to better understand bismuth induced nephrotoxicity for better clinical application of bismuth related compounds.